Interferensi Sintaksis Bahasa Indonesia pada Keterampilan Berbicara Bahasa Inggris Mahasiswa Non-Jurusan Bahasa Inggris - Amir Hamzah; Muhamad Taufik Hidayat; Wahid Hasim (Journal Civics and Social Studies, 2021)
This study aims to analyze the Indonesian language syntactic interference on English Speaking Skills of English Language Students. The research subjects were students of semester 3 at a non-English language college in Garut. This study uses a qualitative descriptive approach with equivalent and distribution methods. Meanwhile, the corpus was obtained by using the listening technique (SBLC), recording and taking notes from students' conversation assignments about their past activities in the form of videos. The results showed that the syntactic interference in this study includes the inaccuracy of word forms that are influenced by the past, inaccurate subject-verb agreements, inaccuracies, absence of articles, sentence patterns that do not match S + V + O, inaccurate use of the words 'no' and 'not'.Keywords: interference, syntax, speaking skills